Queering the palate: The erotics and politics of food in Japanese gourmet manga. Issue 2 (1st November 2020) - Miyajima, Keiko
As demonstrated by a widely circulated Japanese proverb 'men should never enter the kitchen', kitchens, as well as food and the act of cooking, have been deeply suffused with heteronormative gender ideology. While domestic cooking has traditionally been associated with women and femininity in Japanese society and popular media, 'gourmet manga', emerging in shōnen manga in the 1970s, foregrounded male chefs as figures of authenticity and authority, and ever since, have successfully constructed the site of food and cooking as a professional, masculine domain. While shōnen manga tropes of battle, competition and victory have contributed to the construction of hegemonic masculinity in gourmet manga, some popular gourmet manga also employ female bodies to conflate food and sex, by repeatedly showcasing graphically explicit representations of orgasm in the scenes of women eating. These texts promulgate painstakingly prepared food as a catalyst not only for masculine maturity but also for 'healthy' heteronormative desire and, by extension, procreation. However, in more recent gourmet manga, non-competitive, pleasure-based cooking and eating have become salient, along with the gradual diversification of the representations of gender and sexuality. This article examines the queer interrelationship among food, gender and sexuality, in Yoshinaga Fumi's Kinō Nani Tabeta? (What Did You Eat Yesterday?) and Hiiragi Yutaka's Shinmai Shimai no Futari Gohan ('Let's have a meal together'). In these texts, the site of 'gourmet' is relocated from the public/professional to the private/domestic, wherein the pleasures of cooking and eating create new, non-heteronormative forms of intimacy and eroticism. Food is thus redefined as a catalyst for a queer kinship, which enables both the cooks and the eaters to create their own space and time outside the logics of domesticity and reproduction.